Crystal and molecular structure of meso-2,6-dibromoheptanedioic acid (meso-2,6-dibromopimelic acid) - Nathaniel D. A. Dirda; Peter Y. Zavalij; Joseph P. Y. Kao (Acta Crystallographica Section E: Crystallographic Communications, 2016)
The molecular structure of the title compound, C7H10Br2O4, confirms the meso (2R,6S) configuration. In the crystal, molecules are linked by pairs of O—H...O=C hydrogen bonds between their terminal carboxyl groups in an R22(8) motif, forming extended chains that propagate parallel to the c axis. Adjacent chains are linked by C=O...Br halogen bonds.